2011
DOI: 10.1029/2011gl047361
|View full text |Cite
|
Sign up to set email alerts
|

Toward the predictability of meteotsunamis in the Balearic Sea using regional nested atmosphere and ocean models

Abstract: Meteotsunamis are oceanic waves that possess tsunami‐like characteristics but are meteorological in origin. In the western Mediterranean, travelling atmospheric pressure oscillations generate these long oceanic surface waves that can become amplified and produce strong seiche oscillations inside harbors. We analyze a June 2006 meteotsunami event in Ciutadella harbor (Menorca Island, Spain), studying numerically the phenomenon during its full life cycle, from the early atmospheric stages to the atmosphere‐ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 21 publications
1
66
1
1
Order By: Relevance
“…An attempt to take into account the effect of such coupling has so far only been made by Renault et al (2011) for the region of the Balearic Islands, however, simulated ocean wave heights at Ciutadella, the main Balearic meteotsunami "hot spot, " were significantly underestimated. Therefore, this is a principal issue where substantial advancement is needed in the future.…”
Section: Research Gaps and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…An attempt to take into account the effect of such coupling has so far only been made by Renault et al (2011) for the region of the Balearic Islands, however, simulated ocean wave heights at Ciutadella, the main Balearic meteotsunami "hot spot, " were significantly underestimated. Therefore, this is a principal issue where substantial advancement is needed in the future.…”
Section: Research Gaps and Perspectivesmentioning
confidence: 99%
“…Present coupled atmospheric-oceanic models are able to provide qualitative reproduction of meteotsunami waves, but still underestimate their amplitude and the potential for damage (Renault et al, 2011). This is because these models do not describe properly the evolution of tsunamigenic disturbances propagating onshore.…”
Section: Toward Meteotsunami Warning Systemsmentioning
confidence: 99%
“…Based on meteotsunami statistics from Ciutadella inlet, in the Balearic Islands, showed that meteotsunamis with amplitudes higher than 0.2 m, 0.5 m, and 3-4 m ('rissaga' events) occurred every summer, once every 5-6 years, and once every 15-20 years, respectively. Since 1984, the Spanish National Institute of Meteorology has been using weather predictions and numerical simulations to forecast meteotsunamis (Jansa et al 2007;Renault et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric gravity waves are another common cause of meteotsunamis worldwide (Monserrat et al 1991), as exemplified by the 2008 Boothbay event . It is more difficult to parameterize these sources, short of performing high-resolution mesoscale modeling (Renault et al 2011;Vilibić et al 2013;Horvath and Vilibić 2014). In addition, it is unclear if enough data are available to construct distributions of the parameters that control atmospheric gravity waves.…”
Section: Discussionmentioning
confidence: 99%